Development of talent according to Sinti and Calon Romani - Chagas-Ferreira, Jane Farias; Fleith, Denise de Souza; Prado, Renata Muniz (Frontiers in Psychology, 2022)
Intercultural dialogue is a challenging demand for contemporary education, especially concerning the development of talents and potentials. This exploratory qualitative study aimed to identify factors that promote and inhibit the development of Romani talent, in Brazil, according to Sintis and Calons. Two Sinti and five Calon Romani participated in the research, aged 18 to 58 years old, males and females, with educational levels between secondary school and doctorate. A socio-demographic questionnaire and semi-structured interview protocol were used to collect data. The results indicated that talent is recognized as a set of skills associated with musicality, handicrafts, and commerce being linked to traditional Romani crafts. Internal and external inhibitory factors related to prejudice were identified through school, family and community. These barriers affected the self-esteem, personality, ambitions, and perspectives of talented young people. To achieve equity, it is necessary to provide opportunities for exchanging knowledge, practices and perspectives, in order to take into account sociocultural background of minority groups. Future research could compare nomad and non-nomad lifestyles and their impact on talent development.